Synthesis and Application of Polypyrrole/DBSA/Boron Nitride Ternary Composite as a Potential Chemical Sensor for Ammonia Gas Detection - Sambasevam, Kavirajaa Pandian; Suhaimi, Nur Farahin; Mohd Norsham, Izyan Najwa; Shahabuddin, Syed; Raoov, Muggundha; Baharin, Siti Nor Atika (Orbital: The Electronic Journal of Chemistry, 2023)
The present study demonstrates the self-assembly method of chemical oxidative polymerization of polypyrrole (PPy), polypyrrole/boron nitride (PPy/BN), and polypyrrole/dodecylbenzene sulfonic acid/boron nitride (PPy/DBSA/BN) thin films for ammonia (NH3) gas detection. The PPy, PPy/BN, and PPy/DBSA/BN thin films were comprehensively characterized using Attenuated Total Reflectance Fourier-Transform Infrared Spectroscopy (ATR-FTIR), Scanning Electron Microscopy (SEM), X-ray diffractometry (XRD) and conductivity measurement. ATR-FTIR revealed all the pertinent peaks of PPy, BN, and DBSA present in the PPy/DBSA/BN. SEM images of PPy/DBSA/BN depict well-organized morphology. PPy/DBSA/BN recorded the highest conductivity of 4.771 x 10-6 S cm-1 among the prepared polymer thin films. The obtained characterization results are in good agreement with the NH3 gas sensor measurements conducted on the PPy/DBSA/BN composite. The linear correlation coefficient between the two was found to be R2 = 0.9916, indicating a strong relationship. Furthermore, the PPy/DBSA/BN thin film demonstrated a low limit of detection (LOD) of 5.8 ppm, surpassing the OSHA threshold value for NH3 gas. This suggests that the sensor is highly sensitive to trace amounts of NH3 gas. Moreover, the PPy/DBSA/BN thin film exhibited exceptional reusability, with the ability to be used for up to 10 cycles without a significant decrease in performance. The sensor also demonstrated selectivity towards NH3 gas in the presence of common interfering species. Additionally, it exhibited long-term stability, maintaining its performance over a period of 7 days. The proposed self-assembled gas sensor has showcased remarkable performance in detecting NH3 gas at room temperature, making it a promising candidate for industrial applications.